PENGARUH JUMLAH KENDARAAN ANGKUTAN UMUM TERHADAP PENERIMAAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN BERAU - Dandy, Elmansyah (ECO-BUILD, 2018)
The purpose of this study refers to the background and the formulation of problems that researchers proposed is to determine the effect of the number of public transport vehicles to the acceptance Levy Testing Motor Vehicles in the District of Berau during the year 2010 - 2016. There is also a usefulness that researchers expect from the results of this study is to be made as an information material and input for the Government of Berau Regency in the effort to determine the policies related to the business of optimizing the acceptance of Motor Vehicle Testing Test in the future. The result of the research shows that the result of t test is known that the hypothetical that the researcher stated that allegedly the Number of Public Transport Vehicle has significant effect to the acceptance of Retrebusi Testing of Motor Vehicles in Berau District, acceptable. It is biased to see where the tcount (5,624) is greater than the ttable value (2.015). The correlation coefficient value (r) of 0.929 or 92.9% indicates that the relationship between the Number of Public Vehicles (X) on the Receipt of Motor Vehicle Inspection Levies (Y) in Berau District is strong because it is close to one or one hundred percent. Thus, the ups and downs of Motor Vehicle Levies Acceptance is very influential by the ups and downs of the Number of Public Transport Vehicles. The value of coefficient of determination is equal to 0.863 or 86.3%, this figure illustrates that the variation of the rise and fall of the rate of Revenue Levy of Motor Vehicles in the Regency (Y), 86.3% is influenced by the Number of Public Transport Vehicles (X), while the rest of 0.137 or 13.7% is influenced by other factors that are outside the research model.